The Impact of Multinationals along the Job Ladder - Ragnhild Balsvik; Doireann Fitzgerald; Stefanie Haller (Center for Economic Studies and ifo Institute (CESifo), 2023)
Multinational affiliates are more productive than domestic firms, so how do they affect a host country through the labor market? We use data for Norway to show that the labor market is characterized by a job ladder, with multinationals on the upper rungs. We calibrate a general equilibrium job ladder model with endogenous multinational entry to the Norwegian data. In a counterfactual where multinationals face an infinite entry cost, payments to labor fall and profits of domestic firms rise, but the impact is heterogeneous. Competition for workers increases low down on the job ladder, while it decreases high up.
Keywords: E24; F23; F66; J63; J64; 330; multinationals; labor market; job ladder